DEVELOPMENT OF A CANVA-BASED INTERACTIVE E-BOOK ON CLASS XII PETTY CASH FINANCE MATERIAL - Anggraeni, Puspa; Faslah, Roni; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This research is to determine the feasibility and practicality of developing a Canva-based interactive E-Book on class XII petty cash finance material. This research was conducted using the Research and Development method with the Analysis, Design, Development, Implementation, and Evaluation model at SMKN 14 Jakarta, in class XII OTKP with 30 students. The data analysis techniques used are expert validation tests and practicality tests. The expert validation test was carried out by material experts with a percentage of 93.3% categorized as very worthy to use, media experts with a percentage of 86.6% categorized as very worthy to use and learning design experts with a percentage of 98.3% categorized as very worthy to use. In the practicality test carried out by 30 students with a percentage of 96.82% categorized as very practical. The results of this research and development show that the Canva-Based Interactive E-Book on Petty Cash Finance Material for Class XII at SMKN 14 Jakarta is stated worth, and can be used in learning activities. The updated version in this research is by creating an interactive E-book that has two directions of development, there is to make teacher know the extent of students abilities in understanding the subject matter in E-books, and students can understand and directly test their abilities.